2014
DOI: 10.1111/jtxs.12080
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Uniaxial Compression Test of Gellan Gels of Various Mechanical Properties Using Artificial Tongue and Its Comparison with Human Oral Strategy for the First Size Reduction

Abstract: Instrumental compression test using artificial tongue was carried out to compare the fracture profile of gels with the first oral strategy for size reduction by humans (termed as the first size reduction). Gellan gel samples, whose size and shape were the same as those of artificial tongue, were prepared in a wide mechanical range and were compressed uniaxially on artificial tongue at crosshead speed of 10 mm/s. When apparent Young's modulus of artificial tongue was approximately 55 kPa, fracture probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Food texture is a very important cue for human decision‐making to choose an appropriate oral strategy for size reduction, either for tongue–palate compression (for soft foods) or teeth mastication (for hard foods) (Takahashi and Nakazawa ; Arai and Yamada ; Ishihara et al . ). The oral strategy changes from tongue–palate compression to teeth mastication with increasing fracture force in our study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Food texture is a very important cue for human decision‐making to choose an appropriate oral strategy for size reduction, either for tongue–palate compression (for soft foods) or teeth mastication (for hard foods) (Takahashi and Nakazawa ; Arai and Yamada ; Ishihara et al . ). The oral strategy changes from tongue–palate compression to teeth mastication with increasing fracture force in our study.…”
Section: Discussionmentioning
confidence: 97%
“…A similar conclusion was drawn by Ishihara et al . () in which they observed deformation profiles of gels (agar gels or gellan gels) and an artificial tongue (prepared from silicone rubber) using instrumental compression by the artificial tongue, and found that the strain ratio between gels and artificial tongue increased with the decrease of gel fracture force. US elastography is based on the fact that compression produces strain in various tissues and magnitude of the strain is lower in harder tissues than that in softer tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations